Fast and Label-Free Isolation of Circulating Tumor Cells from Blood: From a Research Microfluidic Platform to an Automated Fluidic Instrument, VTX-1 Liquid Biopsy System. (February 2018) - Lemaire, Clementine A.; Liu, Sean Z.; Wilkerson, Charles L.; Ramani, Vishnu C.; Barzanian, Nasim A.; Huang, Kuo-Wei; Che, James; Chiu, Michael W.; Vuppalapaty, Meghah; Dimmick, Adam M.; Carlo, Dino Di; Kochersperger, Michael L.; et al.
Tumor tissue biopsies are invasive, costly, and collect a limited cell population not completely reflective of patient cancer cell diversity. Circulating tumor cells (CTCs) can be isolated from a simple blood draw and may be representative of the diverse biology from multiple tumor sites. The VTX-1 Liquid Biopsy System was designed to automate the isolation of clinically relevant CTC populations, making the CTCs available for easy analysis. We present here the transition from a cutting-edge microfluidic innovation in the lab to a commercial, automated system for isolating CTCs directly from whole blood. As the technology evolved into a commercial system, flexible polydimethylsiloxane microfluidic chips were replaced by rigid poly(methyl methacrylate) chips for a 2.2-fold increase in cell recovery. Automating the fluidic processing with the VTX-1 further improved cancer cell recovery by nearly 1.4-fold, with a 2.8-fold decrease in contaminating white blood cells and overall improved reproducibility. Two isolation protocols were optimized that favor either the cancer cell recovery (up to 71.6% recovery) or sample purity (≤100 white blood cells/mL). The VTX-1's performance was further tested with three different spiked breast or lung cancer cell lines, with 69.0% to 79.5% cell recovery. Finally, several cancer research applications are presented using the commercial VTX-1 system.